Analisis Olah Raga Terhadap Kadar Gula Darah Penderita Diabetes Melitus - Wahyuningsih, Atik Setiawan; Utami, Maria Putri Sari (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2018)
Diabetes mellitus is a degenerative disease that is expected to increase. Lifestyle management is one method to control blood sugar. Exercise regularly can increase insulin sensitivity so that it can help and control blood sugar levels.The purpose was to analyze exercise on blood glucose level of people with diabetes mellitus. Research design was posttest only with control. Population research was diabetes mellitus patient at Puskesmas Ngawi Ngawi District in 2017, used simple random sampling were 82 respondents (41 respondents of control group and 41 respondent of intervention group).Used Mann-Whitney nonparametric statistical test.The results of this study obtained data with average blood sugar levels control group after exercise uncontrolled and average. Data analysis used Mann-Whitney result of p-value 0,000 and value of Z equal to -7,102 which mean there was difference of group blood sugar level.Exercise with high intensity can damage blood sugar levels. Food, consumption of soft drinks and alcohol needs to be considered because it can interfered with the metabolism in the body that can affect blood sugar levels by considering the four pillars of diabetes mellitus management.Â Keywords: Exercise, Blood Sugar Level, Diabetes Mellitus